A review of microscopic interactions between cavitation bubbles and particles in silt-laden flow. (April 2016) - Zhang, Yuning; Zhang, Yuning; Qian, Zhongdong; Ji, Bin; Wu, Yulin
Abstract: Erosion through synergetic effects between cavitation erosion and particle abrasion in silt-laden flow seriously affects the safe operations of hydroturbines. In this review, recent advances of cavitation inception on particles and microscopic interactions between bubbles and particles are reviewed and discussed. For cavitation inception, influences of several paramount parameters (e.g. types, sizes, shape and surface structure of particles, pressurization and memory effects) have been revealed and discussed. The interaction mechanisms between cavitation bubbles and particles are demonstrated using experimental data obtained with a single particle. Through the microscopic interactions, the particles can be accelerated by the collapsing bubbles up to 40 m/s and also be possibly split up by the cavitation, leading to deagglomeration of particle clusters.